Asociación entre la gingivitis y la aparatologia removible en niños entre los 5 y 14 años de edad - López-T., Maria Isabel; Uribe-P., Maria Teresa; Espinal-B., Gabriel Emilio (Revista Facultad de Odontología Universidad de Antioquia, 2016)
The purpose of this study was to evaluate the possible association between removable appliance and the presence of gingivitis. The sample consisted of 260 children (130 children with removable appliance and 130 children without it), aged between 5 and 14, who were treated at the University of Antioquia (school of dentistry). The gingival index from silness and Löe was used to determine the degree of gingivitis. Irztraoral test were performed to determine the type of removable appliance, if any. The results shown no clear correlation between usage ofremovahle appliance and presence of ginigivitis. Neither was relation between the lenght of time the appliance has been used and gingivitis severety degree.